The disappearance of machinery in the Iraqi tax legislation A comparative study - Abd AlBasit Ali AlZobaidi (الرافدین للحقوق, 2006)
As it is known that the value of a firm's fixed assets decreases gradually as a result of the use or expiry of time, the machine used in the enterprise does not always maintain its economic benefit because its value is reduced by the invention of a better the machine. Therefore, the owner of the establishment takes caution and resort to the deduction of annual amounts of its gross profits so that it can then buy new machines, and these amounts deducted for this purpose is deducted from the tax container, because it includes parts of the capital leaked during the production process to the inside and settled, On the profit and not on the capital, so it is necessary to return these amounts to the capital so as not to reach the hands of the tax, so resorted to most of the tax legislation to impose a tax on net income because it is better than the discretionary mandate of the taxpayer and thus achieve tax justice and to maintain the head of the tax The source of income has to take into account the idea of ​​tax costs and we find that the Iraqi tax law has paid attention to the idea of ​​costs in general and in particular.